STRATEGY OF INFORMATION IMPLEMENTATION METHODOLOGY TECHNOLOGIES IN THE LEARNING PROCESS - Poberezhna, N.O. (Pedagogy of Higher and Secondary Education, 2010)
In this article ways of readiness of the future teachers to use of competition technologies in education process are considered.